Dampak dari teknologi digital dan keterampilan abad ke-21 pada kinerja karyawan - Yoma, Fanny Okta; Ranuharja, Fadhli; Fauzihardani, Eka; Rino, Rino (Universitas Negeri Padang, 2025)
In the ever-evolving digital age, it is important to understand the impact of digital technology and 21st century skills on employee performance. In this systematic literature review, researchers explored the relationship between digital technology, 21st century skills and employee performance through synthesizing 24 relevant articles indexed by scopus, google scholar and dimension in the period 2019-2024. The review revealed a number of important insights into how digital technology adoption and 21st century skills development impact employee productivity and effectiveness across a range of organizational contexts. The researcher highlights the salient findings, challenges faced, and practical implications of this research. As such, this article makes an important contribution to our understanding of ways to improve employee performance in the changing digital age, and points the way for future research and practice in this area.